Altered blood and aqueous humor levels of asprosin, 4-hydroxynonenal, and 8-hydroxy-deoxyguanosine in patients with diabetes mellitus and cataract with and without diabetic retinopathy - Oruc, Yavuz; Celik, Fatih; Ozgur, Gokhan; Beyazyildiz, Emrullah; Ugur, Kader; Yardim, Meltem; Aydin, Suleyman (Lippincott Williams and Wilkins, 2020)
Purpose:Diabetic retinopathy (DRP) is the formation of edema and small vessels in the retina due to high blood glucose levels. Asprosin is a hormone that stimulates the release of glucose from the liver into the circulation. Considering the relationship between oxidative stress and DRP, our study aimed to determine the levels of the oxidative stress markers 4-hydroxynonenal (4-HNE) and 8-hydroxy-2?-deoxyguanosine (8-OHdG), as well as asprosin, in the blood and aqueous humor (Aq) of patients with and without DRP.Methods:Thirty patients with single-eye DRP and cataract (DRP + C), 30 patients with diabetes mellitus and cataract without DRP (DM + C), and 30 healthy control (CON) participants were enrolled into this retrospective study. Except for healthy controls, Aq and blood samples were taken from these patients during their cataract operation. Asprosin, 4-HNE, and 8-OHdG concentrations were analyzed using enzyme-linked immunosorbent assays.Results:In patients with DRP, the levels of asprosin, 4-HNE, and 8-OHdG were significantly higher in both Aq and blood samples compared with the group of patients without DRP.Conclusion:These findings suggest that the measurement of asprosin, 4-HNE, and 8-OHdG levels may support clinicians in determining the risk of DRP development. © 2020 Lippincott Williams and Wilkins. All rights reserved.
Keywords: 4-hydroxynonenal; 8-hydroxy-2?-deoxyguanosine; aqueous humor; asprosin; cataract; diabetic retinopathy